Preceramic architecture in the central coast: El Paraíso tradition - Cornejo Maya, Cesar Augusto (2013)
Recent researchs in Pampa de los Perros, a Final Preceramic site located in the lower valley of the Chillón, have revealed a long and complex constructive sequence that includes the building of enclosures, pyramids and a circular plaza. Based on this and in previously published information about contemporary sites with monumental architecture of the Central Coast, and especially from the initial concepts of Ettore Napoli (1967) and Michael Moseley (1992), we specify and extend the concept of El Paraíso Tradition. Furthermore, we propose the relations that this one had with other architectural traditions from Final Preceramic, i.e. with the Traditions Mito and El Aspero. In addition, we raise the relations that this one had with other architectural traditions of the Precerámico Final, that is to say with the i.e. traditions Mito y El Aspero.